Rat models reveal differences in cardiocirculatory profile between Takotsubo syndrome and acute myocardial infarction. Issue 9 (September 2015) - Redfors, Bjorn; Shao, Yangzhen; Ali, Anwar; Sun, Bo; Omerovic, Elmir
<x xml:space="preserve">Abstract</x> Aims Takotsubo syndrome, also known as stress-induced cardiomyopathy, is an important differential diagnosis in patients presenting with chest pain and is associated with significant morbidity and mortality. Beyond adrenergic overstimulation the pathophysiology behind Takotsubo is poorly known and the syndrome cannot be differentiated from acute myocardial infarction (AMI) by non-invasive tests. Despite the facts that Takotsubo syndrome and AMI may differ in many important aspects and that potential mechanistic similarities and/or differences between Takotsubo syndrome and AMI have not been established, Takotsubo syndrome patients are treated according to guidelines developed for AMI and acute heart failure. The aim of this article was to assess whether cardiac function and hemodynamic indices differ between rat models of Takotsubo syndrome and AMI. Methods Male Sprague-Dawley rats were randomized to the Takotsubo syndrome (50 mg/kg intraperitoneally isoprenaline) or AMI [permanent left anterior descending coronary artery (LAD) ligation] models. Two hours post-isoprenaline or LAD ligation, arterial and intraventricular pressures were recorded and cardiac function was studied by echocardiography. In another subset of Takotsubo syndrome rats, pharmacological intervention aimed at maintaining systolic blood pressure more than 90 mmHg with either norepinephrine or phenylephrine was compared with saline. Results Left ventricular end-diastolic pressure was significantly lower and estimates of cardiac function were significantly better in Takotsubo syndrome rats compared with AMI rats. Vasopressor treatment was associated with increased mortality in Takotsubo syndrome rats (P < 0.05). Conclusion Takotsubo syndrome and AMI are associated with different cardiocirculatory profiles. Extrapolation of treatment strategies across the syndromes may therefore not be appropriate.